Peningkatan Pengetahuan dan Minat Radiografer dalam Mengkonsumsi Gizi Seimbang di Era Pandemi COVID-19 - Hidayati, Alpha Olivia; Sari, Ayu Wita (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The consumption of foods that contain balanced nutrition is one way to increase immunity, especially during the COVID-19 pandemic. For this reason, it is necessary to raise awareness of the consumption of food with balanced nutrition for health workers, especially radiographers. One of the efforts that can be done is by providing education to increase radiographer knowledge and interest in consuming foods with balanced nutrition. This community service is in collaboration with IKMARA GUBAYO in the form of online counseling activities. Program evaluation is carried out quantitatively by calculating the frequency distribution of the knowledge level and interest before and after the activity. The results showed an increase in the level of participant’s knowledge about balanced nutrition by 25.45% and an interest in implementing balanced nutrition consumption by 89%. Participant’s knowledge of balanced nutrition increased by 27.4%, knowledge of fixed macronutrient sources, knowledge of vitamin sources increased by 27.4%, knowledge of the benefits of mineral substances increased by 27.2%, and knowledge of how to increase immunity increased by 18.7%. Providing education to radiographers online counseling can increase radiographer’s knowledge and interest in consuming balanced nutrition as an effort to increase immunity during the COVID-19 pandemic.